EKSPLORASI MOTIF BLUE LACE AGATE SEBAGAI HIASAN PADA BUSANA PESTA SIANG - Teni Anggraeni; Pipin Tresna Prihatini (Universitas Pendidikan Indonesia, 2017)
Agate stone is a kind of volcanic stone that is constructed by ossified trickles of lava for thousand years. Agate stone has a special characteristic on its brightful color with special motif that no other stone has. Agate stone is divided by several types, one of the type is blue lace agate which has special characteristic on its wave lace pattern or baby blue ribbons. Color and motif of blue lace agate become a shape inspiration and decoration to make party gown. Party gown is a gown that is wore in a happy moment. Party gown in the afternoon has a characteristic on simple shape that is filled with glamorous embellishments. The luxury of the party gown can be created through several ways such as making decoration using some techniques and materials. One of the techniques of making decoration is using modular technique. Modular is one of the techniques that show the texture which imitates a shape which has shining color and is gradated. The application of this motif shape will influence the way people see towards other’s appearance